Tears of repentance : Christian Indian identity and community in Colonial southern New England - Rubin, Julius H. (University of Nebraska Press, 2013)
This book revisits and reexamines the familiar stories of intercultural encounters between Protestant missionaries and Native peoples in southern New England from the seventeenth to the early nineteenth centuries. Focusing on Protestant missionaries' accounts of their ideals, purposes, and goals among the Native communities they served and of the religion as lived, experienced, and practiced among Christianized Indians, the author offers a means of understanding the motives and motivations of those who lived in New England's early Christianized Indian village communities.